indonesia VARIATION OF CONCENTRATION AND REPEATED USE OF TRIS ACETAT EDTA BUFFER ON DNA TAPE QUALITY Mycobacterium tuberculosis - Makbul Paneja, Rosmini Binti; Rismiarti, Zuri; Indra, Asep Iin Nur; Wahyuni, Yeni (Politeknik Kesehatan Kemenkes Malang, 2024)
Background: Mycobacterium tuberculosis which is resistant to isoniazid (INH) occurs due to gene mutations, mostly in the katG gene. Primers have been found to identify mutations in the katG gene that occur with varying lengths of primer products. However, this has not been proven laboratory-wise. Varying TAE buffer concentrations of 0.5x, 1x, and 1.5x were carried out, and repeated use of TAE buffer. This is to see the effect of concentration variations on the quality of the Mycobacterium tuberculosis DNA band. Method: The type of research used was quasi-experimental. The research subjects used were TAE buffer solution with concentrations of 0.5x, 1x and 1.5x which were used repeatedly at the electrophoresis stage. The examination material was Mycobacterium tuberculosis DNA resulting from PCR. Visualization of electrophoresis results on all samples compared to the size of the ladder used and all products produced are at the appropriate base pair size. Using the ImageJ application in the DNA size analysis process is an alternative that can help assess the size of DNA bands. Research Results: In the results of the research carried out, it was found that the DNA band of Mycobacterium tuberculosis which is resistant to the isoniazid (INH) katG gene for MDR TB is at codon 315 with a product size of 101 bp S315T, 141 bp S315N, 200 bp S315I, 247 bp S315R, 290 bp S315G and 400 bp R463L obtained DNA band density on electrophoresis using a TAE buffer concentration of 0.5x, shown by the highest area formed compared to concentrations of 1x and 1.5x, and from repeated use of TAE buffer twice, visualization of the DNA bands was obtained. still good, it just affects the area of ??the DNA band when read using the ImageJ application. Conclusion: 0.5x TAE buffer concentration is able to provide the highest area compared to 1x and 1.5x TAE buffer concentrations. The repetition process does not affect the visualization of the DNA bands but does affect the smaller area formed. Key words: Electrophoresis; TAE buffer concentration; Mycobacterium tuberculosis; Repeated use of TAE buffer